Responses of an anisotropic magnetoelectroelastic and layered half-space to internal forces and dislocations. (September 2016) - Li, Y.S.; Pan, E.
Abstract: Layered multiferroic heterostructures have applications in various mechanical and electronic devices where the coupling among the mechanical, electric and magnetic fields provides unique opportunity for tailoring the device properties. In this paper, we investigate the coupled magnetoelectroelastic (MEE) field in a layered anisotropic MEE half-space induced by the internal force (traction) and dislocation. Utilizing the Fourier transform and propagator matrix method, we derive the induced field quantities in terms of the Stroh formalism. The analytical solution in the corresponding homogeneous MEE half-space is also derived to remove the concentration/singularity in the layered system. Numerical examples are presented in terms of contours for the extended displacement and stress fields in a three-layered MEE half-space made of piezoelectric and piezomagnetic layers induced by an internal force and dislocation applied over a horizontal circle. These results not only show various interesting features, they can also serve as benchmarks for future numerical analysis and perhaps as guidance for design engineers.